Kośćiół instytucjonalny w krytycznym spojrzeniu dzisiejszych katolików polskich (II) - Baniak, Józef (Polskie Towarzystwo Religioznawcze, 2011)
Józef Baniak – THE INSTITUTIONAL CHURCH IN A CRITICAL VIEW OF TODAY'S POLISH CATHOLICS This article presents the problem of attitudes of today’s Polish Catholics towards the Church, in reference to the outcome of sociological research in this matter. The most difficult part of the adap-tation process of the Church and clergy is the socio-cultural reality started by the changes at the end of the 20th and beginning of the 21st century. In that time in Poland emerged completely new conditions of living, never found before civilization phenomena, but in the first place Poles gained freedom and political independence. These changes significantly influenced their attitudes towards the Church and clergy in the parishes. These attitudes became more critical and unconstrained than it was visible in the time of socialism. Poles become more religiously independent, they reject the moral guidelines of the Church (especially those regarding sexual ethics and family life), the number of Catholics who disbelieve the priests and criticize the hypocrisy and immoral behavior of the clergy had increased. The deepest critique comes from young people, especially regarding the political involvement of the Chu-rch, the pseudo-celibate of the priests and monks, as well the compulsory religion lessons in schools.